2013
DOI: 10.1002/pbc.24758
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial doppler and brain MRI in children with sickle cell disease and high hemoglobin F levels

Abstract: The mild phenotype among Kuwaiti patients with SCD is reflected in normal TCD velocities and a low prevalence of SBI in children with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
5
17
2
Order By: Relevance
“…The earlier study from Kuwait that documented transcranial Doppler findings in pediatric patients with SCD and the predominant AI haplotype did not report any patient with abnormal or conditional velocities in all of the arteries of the circle of Willis that were interrogated. We were not certain whether this finding was a reflection of the rarity of cerebral vasculopathy or whether there is, indeed, a regional or ethnic variation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The earlier study from Kuwait that documented transcranial Doppler findings in pediatric patients with SCD and the predominant AI haplotype did not report any patient with abnormal or conditional velocities in all of the arteries of the circle of Willis that were interrogated. We were not certain whether this finding was a reflection of the rarity of cerebral vasculopathy or whether there is, indeed, a regional or ethnic variation.…”
Section: Discussionmentioning
confidence: 93%
“…The study patients were consecutive patients seen in the Pediatric Hematology Clinics of Al‐Amiri and Mubarak Al‐Kabeer Hospitals in Kuwait, Royal Hospital in Muscat, Oman, Center for Hereditary Blood Diseases, Basra Maternity and Children Hospital in Basra, Iraq, and Tawam Hospital in Al Ain, United Arab Emirates. Although the Kuwaiti patients were part of a previous study, the patients from the other 3 countries had not been reported before. The patients were in a steady state at the time of the study (ie, no crisis, acute illness, or blood transfusion within the preceding 6 weeks).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to the high HbF level, which is generally greater than 30% up to the age of 4 years and remains at about 15% to greater than 20% among adults . This delays the vasculopathy that causes many of the SCD complications such as overt stroke, silent infarcts, acute chest syndrome, priapism, and leg ulcers . In addition, the coexistent β‐thalassemia trait, another modulatory factor, is found in about 40% of Kuwaiti patients …”
mentioning
confidence: 99%
“…9 This delays the vasculopathy that causes many of the SCD complications such as overt stroke, silent infarcts, acute chest syndrome, priapism, and leg ulcers. [10][11][12][13] In addition, the coexistent β-thalassemia trait, another modulatory factor, is found in about 40% of Kuwaiti patients. 6 Sickle cell disease is a progressive disease; the rate of development of various complications is variable; and many patients develop organ damage in adulthood.…”
mentioning
confidence: 99%